2017
DOI: 10.1253/circj.cj-16-0912
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of QRS Duration at Admission for In-Hospital Clinical Outcome of Takotsubo Cardiomyopathy

Abstract: ing, multicenter, population-based cohort database of emergency admissions to acute cardiac care facilities in Tokyo. It was launched in 1978 and expanded to 71 largevolume cardiovascular facilities. We launched the TC research group in 2010 and started collecting data on patients with TC admitted to facilities participating in the Tokyo CCU Network. Data on TC patients were collected retrospectively, and included original copies of ECG for a 3-year period between 2010 and 2012. Data have been collected prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The current major diagnostic criteria for TTS requiring the absence of culprit coronary artery disease make it mandatory to perform CAE before the diagnosis of TTS can be made [2][3][4][5][6][7]. Consequently, all recent studies with relatively large samples (n > 250) enrolled only patients who underwent CAE (mostly CAG) [10,27,28,30,31,[35][36][37][38]. Nevertheless, this and other studies [8,9,39] have shown that a substantial proportion (35-78%) of patients with the diagnosis of TTS received this diagnosis without CAE in real-world clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current major diagnostic criteria for TTS requiring the absence of culprit coronary artery disease make it mandatory to perform CAE before the diagnosis of TTS can be made [2][3][4][5][6][7]. Consequently, all recent studies with relatively large samples (n > 250) enrolled only patients who underwent CAE (mostly CAG) [10,27,28,30,31,[35][36][37][38]. Nevertheless, this and other studies [8,9,39] have shown that a substantial proportion (35-78%) of patients with the diagnosis of TTS received this diagnosis without CAE in real-world clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this and other studies [8,9,39] have shown that a substantial proportion (35-78%) of patients with the diagnosis of TTS received this diagnosis without CAE in real-world clinical settings. These patients who did not undergo CAE were not enrolled in the recent TTS studies [10,27,28,30,31,[35][36][37][38] because they did not fulfill the current diagnostic criteria. Thus, the studies may have underestimated the incidence of TTS due to a selection bias associated with the diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(19) Prolonged QRS duration is also associated with higher in-hospital mortality, cardiac death, ventilator use, ventricular arrhythmias and circulatory failure. (20) Other reported adverse prognostic markers include a higher heart rate and larger sum of ST elevations in all 12 leads. (21) Persistent Q waves are a poor prognostic marker.…”
Section: Qrs Complexesmentioning
confidence: 99%
“…The registry was registered under the University Hospital Medical Information Network Clinical Trials Registry (UMIN000013128) and is described in detail in another study. 10 Since the establishment of the Takotsubo Cardiomyopathy Study Group of the Tokyo CCU Network Scientific Committee in 2010, inpatient data on TTS were collected retrospectively between 2010 and 2012. Since 2013, inpatient data on TTS have been collected prospectively.…”
mentioning
confidence: 99%